Torque Transmission and Rotational Response Characteristics of Medical Guide-wire in Curved Blood Vessel Model (Journal of Fiber Bioengineering and Informatics, 2012)
In order to provide the basic data for the development of medical guide-wire and a simulator for thePTCA (Percutaneous Transluminal Coronary Angioplasty), we have developed the blood vessel modelmade of PVA hydrogel and investigated the mechanical characteristics of guide-wire in the blood vesselmodel. In the present study, we discussed the characteristics of torque transmission and rotationalresponse of the guide-wire in curved blood vessel model with change in the PVA concentration of thehydrogel and thickness of blood vessel model.